The Effect of Pre-Service Cognitive and Pedagogical Teacher Skills on Student Achievement Gains: Evidence from German Entry Screening Exams - Bernhard Enzi (ifo Institute - Leibniz Institute for Economic Research at the University of Munich, 2017)
Information about teachers' effectiveness at the hiring stage is particularly scarce despite its importance for personnel decisions. Using the German setting of teacher training, I investigate the relationship of teachers' pre-service cognitive and pedagogical skills as measured by two state examinations and the high-school GPA on later effectiveness. I apply standard value-added models to rich German student-achievement panel data and find that being in the top quartile in these skill domains is linked with significantly higher teacher effectiveness. Better teacher skills are associated with a more efficient way of classroom management.
Keywords: I21; J24; J45; H75; 330; Teacher; value-added; cognitive skills; student achievement